Differing effects of grass and polythene mulches on sweet potato productivity in derived savannah agro-ecology - Amuji, Felix; Ezema, Perpetual; Osadebe, Vivian; Obi, Justina; Obalum, Sunday (International Journal of Horticultural Science, 2025)
Sweet potato as a food crop that is grown for both its tuberous roots and vegetative parts, the latter of which also serves as animal feed. Its production in the savanna regions can be limited by high evaporative demand, especially where soils with low water retentivity are involved. This work studied the effects of various locally available polythene as mulch materials for sweet potato growth in derived savanna agro-ecology. An experiment was thus conducted at Nsukka, a derived savannah in southeastern Nigeria, with orange fleshed variety of sweet potato. Treatments were polythene mulches of contrasting colours (black, white, red and blue polyethylene), including also organic mulch (dry grasses) as reference and a no-mulch control. The experiment was executed in two successive cropping seasons, and the data averaged and analysed. Agronomic and weed incidence data collection was done fortnightly from 2nd to 10th week of planting. The results showed that the polythene mulches (especially the black one) were better in the control of weeds. Furthermore, the sweet potato yields were affected significantly (p < 0.05) by mulching on the total number of tubers for each plant with grass-mulched plots showing the highest value (36) and transparent polyethylene-mulched plots the lowest (19). Also, total weight of tubers per plant at harvest differed (p < 0.05), with grass-mulched plots showing the highest value (2.39 kg), followed by the control (no mulching) plots (1.62 kg), then the coloured polyethylene mulched plots with the red polyethylene-mulched plots as the lowest (0.64 kg). This study recommends the use of organic mulch or no mulching in sweet potato production in this agro-ecological zone as they produced the best yields.